2021
DOI: 10.1097/md.0000000000024898
|View full text |Cite
|
Sign up to set email alerts
|

A novel biomarker, MRPS12 functions as a potential oncogene in ovarian cancer and is a promising prognostic candidate

Abstract: Ovarian cancer (OC) is the leading cause of gynecological cancer deaths. Extraordinary histologic and genetic heterogeneity presents as great hurdle to OC's diagnosis and treatment. MRPS12 (Mitochondrial Ribosomal Protein S12), encoding a 28S subunit protein, controls the decoding fidelity and susceptibility to aminoglycoside antibiotics. Our study aims to investigate the clinical significance and potential mechanism of MRPS12 in OC. Oncomine, Tumor Immune Estimation Resource database (TIMER), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…As illustrated here for one case of prostate cancer, and in previous papers on cases of papillary thyroid cancer [ 46 , 92 ] and clear cell renal cell carcinoma [ 35 , 93 ], GFP offers a comprehensive personalized alternative to the biomarkers approach to determine the cancer transcriptional identity (e.g., [ 112 ]) and explore gene therapy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As illustrated here for one case of prostate cancer, and in previous papers on cases of papillary thyroid cancer [ 46 , 92 ] and clear cell renal cell carcinoma [ 35 , 93 ], GFP offers a comprehensive personalized alternative to the biomarkers approach to determine the cancer transcriptional identity (e.g., [ 112 ]) and explore gene therapy.…”
Section: Discussionmentioning
confidence: 96%
“…REV analysis pointed also to some interesting genes for oncogenomics. Thus, MRPS12 , the most stably expressed gene in “N”, is a potential prognostic candidate for ovarian cancer [ 92 ], while UXT the most unstably expressed gene in “N” is associated with advanced stages of gastric cancer [ 93 ]. ENTPD2 , the most stably expressed gene in “A” is a biomarker for lung [ 94 ] and hepatocellular [ 72 ] carcinomas, while USP31 , the most variably expressed gene in “A”, could be a potential target for sarcomas [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“… Liu et al (2020) found that POLR2L displayed a correlation to survival duration and alternative splicing in lung squamous cell carcinoma patients. MRPS12 functioned as an oncogene and a prognostic candidate in ovarian carcinoma ( Qiu et al, 2021 ). DYNLL1 hypomethylation and upregulation was characterized by stage- and grade-dependent manners and correlated to unfavorable survival outcomes in HCC ( Berkel and Cacan, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, MRPL15 is a new prognostic indicator and therapeutic target for epithelial ovarian cancer [ 26 ]. MRPS12 is a potential oncogene of ovarian cancer [ 27 ], while MRPL27 displays an adverse effect on the overall survival rate and disease-free survival rate of cholangiocarcinoma patients [ 28 ]. MRPL42 is activated by YY1 to promote the progression of lung adenocarcinoma [ 29 ].…”
Section: Discussionmentioning
confidence: 99%